+0  
 
0
236
1
avatar

how do i convert y=(8/-3)x-(2/3) into Ax+By=C

Guest Sep 16, 2017
 #1
avatar+7266 
+1

Ax + By  =  C

 

Since  C  is alone on one side of the equation, let's first solve for  the "C" in our equation, which is the number that is not being multiplied by a variable:  -(2/3)

 

y  =  (8/-3)x - (2/3)

                                           Subtract  (8/-3)x  from both sides of the equation.

-(8/-3)x + y  =  -(2/3)

                                           -(8/-3)  =  8/3

(8/3)x + y  =  -(2/3)

 

Now....as it is.....  A = 8/3 ,  B = 1 ,  and  C = -2/3  .

But I think you want A, B, and C to be integers. So let's multiply through by  3  to clear the fractions.

 

8x + 3y  =  -2

hectictar  Sep 16, 2017

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.